Energy aware resource association in RIS assisted VLC-RF communication network - Ashu Taneja; Ali Alqahtani; Nayef Alqahtani (PLoS ONE, 2025)
Owing to the rapid surge in the number of intelligent devices and data-intensive applications, the demand for reliable communication support has increased. This has put an undue burden on the radio frequency (RF) based communication which suffers from the main challenge of limited spectrum and access congestion. This is overcome with the use of visible light communication (VLC) that offers broader spectrum and high speed data transmission. However, the finite coverage and susceptibility to blockages in VLC can be avoided with optical reconfigurable intelligent surfaces (ORISs), which alter the wireless propagation channel. This paper presents an integrated VLC-RF communication network aided with ORISs and an RF RIS. To support the network communication a resource association algorithm is proposed that associates a set of ORISs to each VLC access point (AP) and node pair. The impact of power allocation on the system performance is also evaluated. It is observed that the presented hybrid system model achieves sum rate gain of 9.43% with equal power allocation. Also, the proposed association scheme improves the total power consumption by 12.74%.